PEMAHAMAN KONSEP BENTUK DAN FUNGSI BAGIAN TUMBUHAN MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING SISWA KELAS IV SD - Sri Herlina; Jajang Bayu Kelana (COLLASE (Creative of Learning Students Elementary Education), 2021)
This research was motivated by the low understanding of science concepts in elementary schools. The method used in this research is descriptive qualitative research method. The study population was the fourth-grade students of SDN 3 Cikahuripan Lembang, West Bandung Regency. while the selected sample was 34 students with convenience technique. The result of this research is the increase in students' conceptual understanding. The study concluded that the Problem Based Learning learning model affected an increasing understanding of the concept of science